The extra connectivity of enhanced hypercubes. Issue 1 (2nd January 2020) - Li, Jin'e; Huang, Yanze; Lin, Limei; Yu, Hui; Chen, Riqing
ABSTRACT: Connectivity plays an crucial role in measuring the fault tolerance of a multiprocessor system in the case of vertices failures. Extra connectivity is an important indicator of a network's ability for diagnosis and fault tolerance. In this paper, we analyse the fault tolerance ability of the n, k -dimensional enhanced hypercube, a well-known interconnection network denoted by Q n, k proposed for multiprocessor systems, and establish the { 1, 2, 3 } -extra connectivity of Q n, k . GRAPHICAL ABSTRACT: